Penerapan Model UTAUT dalam Menjelaskan Faktor Minat dan Penggunaan Sistem Informasi Manajemen Daerah - Nugraha, Gde Sandita; Yadnyana, Ketut (E-Jurnal Akuntansi, 2018)
The success of an accounting information system in managing regional finances in government agencies is very important to note. Success or failure of the system used can affect the performance of employees in these agencies. The purpose of this research is to examine the interest of using and utilizing SIMDA with UTAUT model. The results of the analysis found that there was an influence between the variables of performance expectation on the interest of the user, the business expectation on the utilization interest, the social factor on the utilization interest, the conditions that facilitate the usage, training on the usge, the interest of utilization on the use. To cultivate the interest and usage of SIMDA it is very important to conduct a training program for all employees in Gianyar District Secretariat in order to assist in input process at SIMDA can be faster Keywords: performance expectations, business expectations, social factors, facilitating conditions, training, interest in utilization, and use